2019
DOI: 10.1108/ijssp-05-2019-0093
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of student engagement on social network sites and academic performance of medical students

Abstract: Purpose In the recent times social media is considered as the most popular tool of communication among the students in India. Based on the assumption that the usage of social media is going to reinforce the academic performance among the medical students, the purpose of this paper is to investigate the mediating effect of student engagement on the use of SM and AP of medical students of India. Design/methodology/approach The students were selected from the top three public-funded medical colleges of India. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Studies in this review demonstrated that cognitive engagement of medical students correlated with knowledge-based achievement. 59,62,73,75 Similar relationships between cognitive engagement and academic achievement have been also established in college students 87 as well as in high school students. 88 On the other hand, the relationships between academic achievement and other dimensions of engagement are fuzzy.…”
Section: Outcomes Of Student Engagementmentioning
confidence: 67%
See 4 more Smart Citations
“…Studies in this review demonstrated that cognitive engagement of medical students correlated with knowledge-based achievement. 59,62,73,75 Similar relationships between cognitive engagement and academic achievement have been also established in college students 87 as well as in high school students. 88 On the other hand, the relationships between academic achievement and other dimensions of engagement are fuzzy.…”
Section: Outcomes Of Student Engagementmentioning
confidence: 67%
“…As shown in Figure 2 (upper panel), most of the articles (94.1%, n = 48) are published in the last 8 years. The lower panel of Figure 2 shows that 47.1% ( n = 24) of the studies are conducted in the United States, 26–49 9.8% ( n = 5) in the United Kingdom, 50–54 9.8% ( n = 5) in Australia, 55–59 4% ( n = 2) in Germany, 60,61 4% ( n = 2) in the Netherlands, 62,63 2% ( n = 1) in Canada, 64 2% ( n = 1) in Norway, 65 2% ( n = 1) in Ireland, 66 5.8% ( n = 3) in China, 67–69 4% ( n = 2) in Turkey, 70,71 2% ( n = 1) in Pakistan, 72 2% ( n = 1) in Malaysia, 73 2% ( n = 1) in Korea, 74 2% ( n = 1) in India 75 and 2% ( n = 1) in Brazil 76 . The methodology in the included studies were quantitative in 66.7% ( n = 34), qualitative in 11.8% ( n = 6) and mixed methods in 21.6% ( n = 11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations